2010
DOI: 10.1002/pola.23875
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and nonlinear optical properties of novel Y‐type polyurethane containing tricyanovinylthiazole with enhanced thermal stability of second harmonic generation

Abstract: A novel Y-type poly [iminocarbonyloxyethyl-5-methyl-4-{2-thiazolylazo-4-(1,2,2-tricyanovinyl)}resorcinoxyethyloxycarbonylimino-(3,3 0 -dimethoxy-4,4 0 -biphenylene)] 4 containing 5methyl-4-{5-(1,2,2-tricyanovinyl)-2-thiazolylazo}resorcinoxy groups as nonlinear optical (NLO) chromophores, which constitute part of the polymer backbone, was prepared and characterized. Polyurethane 4 is soluble in common organic solvents such as acetone and N,N-dimethylformamide. It showed a thermal stability up to 250 C in thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Before poling, the films appeared very flat and clean. After poling, however, the films were changed, and numerous hills and valleys appeared on the poled films, which could be seemed as the evidence of the chromophores alignment during the poling process . The AFM images further indicate that the synthesized EO polycarbonates have excellent film‐forming properties, it also demonstrated that the materials have excellent dielectric strength because good film quality was retained after high electric field poling according to the AFM scans of the poled films.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Before poling, the films appeared very flat and clean. After poling, however, the films were changed, and numerous hills and valleys appeared on the poled films, which could be seemed as the evidence of the chromophores alignment during the poling process . The AFM images further indicate that the synthesized EO polycarbonates have excellent film‐forming properties, it also demonstrated that the materials have excellent dielectric strength because good film quality was retained after high electric field poling according to the AFM scans of the poled films.…”
Section: Resultsmentioning
confidence: 88%
“…Atomic force microscope (AFM) is usually used to investigate the surface morphology of polymer films. It could reveal the domain structures of NLO chromophores, the film‐forming properties, and the differences of the films morphology before and after poling . Figure shows the AFM scans of the spin‐coated films of PC‐TCFC‐2 and PC‐DFTC‐3 before and after poling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Petroff et al used the same strategy and created polar molecules doped polydimethylsiloxane (PDMS) foams and measured the electrical and mechanical properties and by tuning these properties they achieved a maximum d 33 piezo-coefficients about 153 pCN −1 [4]. Furthermore, many researchers showed that the inclusion of polar molecules in polyurethane can create either high piezoelectricity or NLO materials [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. We motivated by reviewing the previous works to do further experiments to observe the effect of polar moieties on other properties of polyurethane.…”
Section: Introductionmentioning
confidence: 99%
“…Physically crosslinked systems via hydrogen bonds have advantages such as homogeneity and good processability relative to chemically crosslinked systems, which suffer from significant optical loss and poor solubility. Recently we prepared novel polyurethanes containing tricyanovinylthienylresorcinol, tricyanovinylthienylcatechol, tricyanovinythiazolylazoresorcinol and nitrophenylazoresorcinol as NLO chromophores. The resulting polymers exhibit enhanced thermal stability of second harmonic generation (SHG), which stems from the stabilization of the dipole alignment of the NLO chromophores at high temperature.…”
Section: Introductionmentioning
confidence: 99%